OC-061 A prospective multi-national study of the colorectal cancer mucosal microbiome reveals specific taxonomic changes indicative of disease stage and prognosis. (17th June 2017) - Alexander, J; Perdones-Montero, A; Scott, A; Poynter, L; Atkinson, S; Soucek, P; Hughes, D; Susova, S; Liska, V; Goldin, R; Marchesi, J; Kinross, J; et al.
Abstract : Introduction: The colorectal cancer (CRC) microbiome is niche specific and individualised. Several putative driver organisms enriched on CRCs have been identified from human studies, but few data exist which properly account for important clinical variables in CRC. In this study, we used a meta-taxonomic approach to demonstrate how the CRC microbiome varies with disease stage, histological markers of prognosis and host molecular phenotypes. Method: A prospective study was performed on patients undergoing colonoscopy and elective surgery for CRC at three hospitals in UK and Czech Republic. Tissue was sampled from tumours, adenomas, adjacent normal mucosa and mucosa from healthy colon controls. The V1-2 regions of the 16S rRNA gene were sequenced (Illumina MiSeq); data were processed in Mothur and analysed in Stamp and R. Species assignment was performed with NCBI BLAST for microbial genomes. False discovery rate p value correction accounted for multiple testing. Histological analysis and tumour molecular phenotyping were performed according to Royal College of Pathology guidelines. Results: One hundred and ninety six patients were recruited: 158 CRC patients, 24 adenoma patients and 14 normal colon controls (median age 70; range 35–90). Tumours were staged as 6 T0, 4 T1, 23 T2, 97 T3, 27 T4; 99 N0, 40 N1, 27 N2; 6 M1. No significant differences were seen in diversity or taxonomy between the UK and Czech cohorts. Adenoma and healthy colon control samples were taxonomically indistinct. However, CRCs were characterised by reduced Shannon diversity (p<0.01), with enrichment of organisms including Bacteroides fragilis, Fusobacterium nucleatum and under-representation of Bacteroides vulgatus, Bacteroides uniformis and Faecalibacterium prausnitzii (all q<0.01). Furthermore, we found a significant progressive reduction in the expression of Bacteroides vulgatus with advancing T stage and a corresponding increase in Fusobacterium nucleatum expression (figure). Additionaly, samples from patients with T4 tumours and cancers expressing histological and molecular markers of poor prognosis were characterised by enrichment of certain low abundance oral pathobionts: Parvimonas micra, Porphyromonas gingivalis and Prevotella spp. Conclusion: This large prospective analysis demonstrates that the CRC microbiome is stage-specific and appears to evolve with disease progression. We conclude that oral pathobionts which colonise advanced stage disease relate to markers of tumour prognosis, raising the possibility that they may be directly influencing tumour invasion. Disclosure of Interest: None Declared